Third life of grange copeland ebook - Walker, Alice (Open Road Media, 2011)
From the New York Times –bestselling author of The Color Purple : A “moving, tender” novel of a Deep South tenant farmer’s quest for a new life ( Publishers Weekly ). Grange Copeland, a deeply conflicted and struggling tenant farmer in the Deep South of the 1930s, leaves his family and everything he’s ever known to find happiness and respect in the cold cities of the North. This misadventure, his “second life,” proves a dismal failure that sends him back where he came from to confront his now-grown-up son’s disastrous relationships with his own family, including Grange’s granddaughter, Ruth Copeland, a child that Grange grows to love. Love becomes the substance of his third and final life. He spends it in devotion to Ruth, teaching and protecting her—though the cost of doing so is almost more than he can bear. From a Pulitzer Prize and National Book Award winner, this is an “honest sensitive tale . . . leavened by those moments of humor and warmth that have enabled men and women to endure so much tragedy” ( Chicago Daily News ).   This ebook features an illustrated biography of Alice Walker including rare photos from the author’s personal collection.